2014
DOI: 10.1111/nmo.12356
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic receptor subtypes mediating relaxation of the normal human clasp and sling fibers of the upper gastric sphincter

Abstract: Background Proper function of the gastroesophageal high pressure zone is essential for the integrity of the antireflux barrier. Mechanisms include tonic contractions as well as the decreased tone during transient lower esophageal sphincter relaxations. Methods We characterized the pharmacology of nicotinic receptors mediating relaxations of the human upper gastric sphincter (clasp and sling fibers) using currently available subtype selective nicotinic antagonists in tissue from organ transplant donors. Donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Thus, the amount of muscle involved in generating the force is very similar for all strips regardless of strip size. Use of this methodology also matches previously reported methods from our laboratory ( 19 , 33 , 34 ).…”
Section: Methodssupporting
confidence: 78%
“…Thus, the amount of muscle involved in generating the force is very similar for all strips regardless of strip size. Use of this methodology also matches previously reported methods from our laboratory ( 19 , 33 , 34 ).…”
Section: Methodssupporting
confidence: 78%
“…The action of swallowing has been shown to stimulate the afferent and efferent vagal nerves (Hornby and Abrahams, 2000). Indeed, stimulation of the nicotinic acetylcholine receptor is responsible for relaxation of the LES (Kadakia et al, 1996;Ruggieri et al, 2014). Accumulated evidence has shown that the relaxant responses to vagal stimulation are reduced by interfering with neurotransmitters, including nitric oxide (NO) (Kawahara et al, 1997;Paterson et al, 1992) and vasoactive intestinal polypeptide (VIP) (Rattan, 1986), in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%